Impact of recent legislative bills regarding clinical research on Italian ethics committee activity. Issue 10 (30th September 2008) - Porcu, L; Poli, D; Torri, V; Rulli, E; Di Tullio, M C; Cinquini, M; Bajetta, E; Labianca, R; Di Costanzo, F; Nitti, D; Floriani, I
Abstract : Aims and background: The present work assessed the impact of two decrees on ethics committees in Italy, aimed at bringing the national laws on the conduct of clinical trials into line with the rest of the EC, and regulating and facilitating not-for-profit research. Material and methods: Prospectively collected data from an Italian multicentre study were examined with respect to the ethics review process. Administrative and time elements of the review process were audited. Main outcome measures were time between the application submission and the ethics committee definitive opinion, type and number of application submission forms, number of ethics committees that refused fee exemption, and time between the ethics committee approval and the administrative authorisation. Results: A total of 134 local research ethics committees (LRECs) were approached. Application submission procedures and application forms varied greatly; paper submission was mandatory. The median time from submission to approval was 72 days. Only two LRECs refused the fee exemption. The median time from LREC approval to administrative agreement was 50 days and only 9.6% of local authorities came to a verbal agreement with the sponsor. Conclusions: Italian LRECs are still not sufficiently efficient in complying with the Directive 2001/20/EC requirement (60 days). Better coordination of LRECs work is needed although the optimal level of coordination between them is still not known. In the meantime, national guidelines are needed concerning the application of Directive 2001/20/EC. The behaviour of Italian LRECs towards not-for-profit research was excellent although only the fee exemption was requested.